PERLINDUNGAN HUKUM TERHADAP PENGGUNA JASA TITIP (JASTIP) MELALUI MEDIA ONLINE - Monarchi, Try Krisna; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Development of online shopping systems has created new business opportunities, one of which is known by the public as entrusted services. A entrusted service is a job in and out of a shop, mall or wholesaler with certain brands according to the desires of customers who believe in their services. The goods you are looking for are not only at the local level, there is often a demand for goods from abroad. The entrusted service profession uses a very simple working mechanism. The position of an entrusted service is a third party between the seller and the buyer, but the main task of entrusting services is the shopper for the entrusters. Jastip, which is short for